Load Flow Analysis for Process – Tank Loading Power Generation Networks Interconnection - Radita Arindya (International Journal of Applied Power Engineering (IJAPE), 2014)
Establishment of interconnection links between Process -Tank Loading electrical networks bring some advantages as there are excess capacity at Process which can be utilized in principle to feed Tank Loading. Some result of power system study will be as an input for operational purposes. Concerning Motor Starting Studies and Load Flow Studies and taking into account that the transformer is off load tap changing, the best tapping position for Isolation Transformer is at -5% (primary side).  The best technical power generation configuration is proposed with configuration 2 (two) Process -TEG and 1 (one) Tank Loading-TEG running with 2 (two) interconnection, provided with appropriate load shedding system. Bare in mind that during smooth power transfer from each Process-TEG which requires 3 (three) Process-TEG running in parallel, there is an issue on kA capacity of Process switchgear. Existing setting of protection relay shall be reviewed according to the result of protection coordination study